Correlation of skeletal muscle blood oxygenation level‐dependent MRI and skin laser doppler flowmetry in patients with systemic sclerosis. Issue 6 (25th November 2013) - Partovi, Sasan; Schulte, Anja‐Carina; Staub, Daniel; Jacobi, Bjoern; Aschwanden, Markus; Walker, Ulrich A.; Imfeld, Stephan; Broz, Pavel; Benz, Daniela; Zipp, Lisa; Takes, Martin; Jäger, Kurt A.; et al.
<x xml:space="preserve">Abstract</x> Purpose To investigate the origin of skeletal muscle BOLD MRI alterations in patients with systemic sclerosis (SSc) by correlating BOLD MRI T2* signal of calf muscles with microcirculatory blood flow of calf skin measured by laser Doppler flowmetry (LDF). Materials and Methods BOLD MRI (3T) and LDF measurements were performed in 12 consecutive SSc patients (6 women, 6 men; mean age 54.0 ± 10.0 years) and 12 healthy volunteers (4 men, 8 women; mean age 44.7 ± 13.1 years). For both modalities, the same cuff compression paradigm at mid‐thigh level was used. LDF datasets were acquired using a PeriScan PIM II Imager (Perimed AB, Stockholm, Sweden) at the upper calf corresponding to the level of MR imaging. Cross‐correlations of BOLD and LDF signal intensity changes depending on time lags between both time series were calculated. Results Maximal cross‐correlations of BOLD T2* and LDF measurements were calculated as 0.93 (healthy volunteers) and 0.94 (SSc patients) for a BOLD time lag of approximately 10 s. Key parameter analysis suggested that in contrast to hyperemic BOLD signal loss at maximum value in SSc patients, ischemic T2* decrease cannot be explained by differences of tissue perfusion. Conclusion Skeletal muscle BOLD T2* signal in SSc patients is closely correlated with changes of microperfusion as detected by LDF.J. Magn. Reson. Imaging 2014;40:1408–1413. © 2013 Wiley Periodicals, Inc.